The Legal Implications of Acquittal for Criminal Acts of Abuse Based on the Principle of Justice - Hania Wulandari; Abdul Kholiq (Jurnal Daulat Hukum, 2025)
In the modern era, criminal cases have become more complex and abuse remains one of the most frequently encountered offenses in court proceedings. The enforcement of criminal law rests on the presumption of innocence, meaning that prosecutors must prove the defendant’s guilt beyond reasonable doubt. If the evidence is insufficient, the judge must acquit the defendant. However, such acquittals often create a dilemma of justice, especially when victims have clearly suffered harm but the legal elements of the offense cannot be proven. The Lubuklinggau District Court Decision No. 186/Pid.B/2023/PN Llg serves as a significant example. In this case, the panel of judges acquitted the defendants even though witness statements and a Visum et Repertum (medical report) were presented. The judges reasoned that the connection between the pieces of evidence was not strong enough to establish the defendants’ direct involvement in the abuse. This study analyzes the judges’ considerations in issuing the acquittal and examines its implications for victims’ rights from the perspective of justice. The findings show that the acquittal was based on the failure to prove the element of “jointly committing abuse.” Although Yoyon Utoyo was found to have committed violence against the victim, Hengki Ternando, there was no concrete evidence linking Bobot Sudoyo to the act, so the element of deelneming (participation) was not fulfilled. Legally, the verdict is valid since the elements of the crime were not proven beyond reasonable doubt. Yet from the victim’s viewpoint, the decision is unjust, as it denies protection and recovery rights guaranteed under Law No. 31 of 2014 on Witness and Victim Protection. This case reflects the tension between legal certainty and justice, where formal procedures often overshadow fairness, weakening public trust in the judiciary.